Marketing Strategies for Promoting Medical Tourism in Thailand / Jutamas Rerkrujipimol and Ilian Assenov - Rerkrujipimol, Jutamas; Assenov, Ilian (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2011)
Thailand is considered to be among the global leaders in the medical tourism market which has grown rapidly in recent years but has faced formidable competition from Singapore, India and other countries. This exploratory research was intended to evaluate the current marketing strategies of healthcare providers and intermediaries through interviews with stakeholders and observation, and to propose effective marketing strategies for preserving and enhancing Thailand's position as a leading medical tourism destination. The paper identifies the strengths of Thailand's healthcare service providers and points to a number of problems that may reduce the growth opportunity of this industry. These include lack of practical government policies with regard to medical tourism and of other supporting regulations, lack of organization as a cooperation centre aimed at promoting the medical tourism industry as a whole, remaining low awareness of the opportunities presented by the industry among potentialfbreign patients, and a shortage of doctors and qualified medical staff. Measures for improvement are suggested.